2009
DOI: 10.1089/vbz.2008.0110
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Genetics of Raccoons (Procyon lotor) Associated with Ridges and Valleys of Pennsylvania: Implications for Oral Rabies Vaccination Programs

Abstract: Raccoons are the reservoir for the raccoon rabies virus variant in the United States. To combat this threat, oral rabies vaccination (ORV) programs are conducted in many eastern states. To aid in these efforts, the genetic structure of raccoons (Procyon lotor) was assessed in southwestern Pennsylvania to determine if select geographic features (i.e., ridges and valleys) serve as corridors or hindrances to raccoon gene flow (e.g., movement) and, therefore, rabies virus trafficking in this physiographic region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
4
24
1
Order By: Relevance
“…Surprisingly, this value is higher than those reported for raccoon populations sampled over both larger (Cullingham et al 2008; F ST range 0.0095-0.0163) and similarsized (Root et al 2009; F ST = 0.0019) geographic areas, using microsatellite loci with high allelic richness, than that sampled in this study. Examination of genetic differentiation among neighborhood pairs revealed high variability in levels of genetic differentiation we detected among neighborhood pairs (-0.004 F ST 0.056), with only 41% of 406 pairwise comparisons exhibiting statistically significant levels of genetic differentiation.…”
Section: Figcontrasting
confidence: 93%
“…Surprisingly, this value is higher than those reported for raccoon populations sampled over both larger (Cullingham et al 2008; F ST range 0.0095-0.0163) and similarsized (Root et al 2009; F ST = 0.0019) geographic areas, using microsatellite loci with high allelic richness, than that sampled in this study. Examination of genetic differentiation among neighborhood pairs revealed high variability in levels of genetic differentiation we detected among neighborhood pairs (-0.004 F ST 0.056), with only 41% of 406 pairwise comparisons exhibiting statistically significant levels of genetic differentiation.…”
Section: Figcontrasting
confidence: 93%
“…The haplotype composition and low effective population size, combined with the high density of raccoons in Germany (Hohmann 2001), rather argue for interbreeding of related individuals and against multiple sources of introduction of individual populations. The level of intrapopulation genetic diversity, expressed as expected heterozygosity values and allelic richness, are comparable with those reported for raccoon populations in the native species range (Cullingham et al 2006, 2008a, Root et al 2009, Hauver et al 2010, Santonastaso et al 2012. Four of the loci analysed in this study were also used to reveal the genetic diversity of raccoons in the native range.…”
Section: Mitochondrial Diversitysupporting
confidence: 79%
“…In addition, these populations likely interact at habitat interfaces. Although some evidence of isolation by distance has been noted for raccoons in this area (Root et al 2009), raccoons do not necessarily need to disperse into other areas (e.g., one valley to another) to develop a panmictic population or to transmit rabies virus. For example, if raccoons from LV come into contact with raccoons on LR, and those raccoons in turn come into contact with raccoons from JV, these interactions could produce a seemingly panmictic population and enable rabies virus transmission among the three populations.…”
mentioning
confidence: 84%
“…2). However, these results should be interpreted with caution over the long-term, as a landscape genetics study of raccoons conducted in the same general area suggested that there was one essentially panmictic population of these animals in this area with no obvious hindrances or corridors to movement (Root et al 2009). Thus, although this study suggests that raccoons seldom move from one valley to the next over the short-term, it most certainly happens on occasion.…”
mentioning
confidence: 90%
See 1 more Smart Citation